تحديات السقف الزجاجي من وجهة نظر القيادات الأكاديمية النسائية بجامعة الملك خالد - آل هيضة، حنان محمد عبدالله (جامعة الإمام محمد بن سعود الإسلامية, 2022)
هدفت الدراسة الحالية إلى التعرف على تحديات السقف الزجاجي من وجهة نظر القيادات الأكاديمية النسائية بجامعة الملك خالد، والكشف عن الفروق الإحصائية بين متوسط استجابات مفردات عينة الدراسة حول تحديات السقف الزجاجي، والتي تعزى إلى اختلاف متغيرات: (المنصب القيادي، الدرجة العلمية، عدد سنوات الخبرة في مجال العمل القيادي). إضافة إلى التعرف على سبل التغلب على التحديات التي تواجه القيادات الأكاديمية النسائية من وجهة نظرهن. ولتحقيق هدف الدراسة؛ فقد تم استخدام استبانة مكونة من (33) عبارة موزعة على محورين؛ هما: (بعد التحديات المهنية -بعد التحديات الشخصية). وتم توزيعها على عينة من القيادات الأكاديمية النسائية بكليات جامعة الملك خالد، بلغت (46) قائدة أكاديمية. وتوصلت الدراسة إلى مجموعة من النتائج؛ أهمها: أن مفردات عينة الدراسة قد أعطت درجة موافق (بدرجة عالية) على وجود التحديات المهنية، ودرجة موافق (بدرجة منخفضة) على وجود التحديات الشخصية، ودرجة موافق (بدرجة عالية) على سبل التغلب على التحديات التي تواجه القيادات الأكاديمية النسائية بالجامعة. كما أثبتت الدراسة عدم وجود فروق ذات دلالة إحصائية لجميع متغيرات الدراسة. وفي ضوء النتائج قدمت الدراسة عددا من التوصيات. This study aimed to identify the challenges of the glass ceiling from the point of view of women academic leaders at King Khalid University. And to reveal the statistical differences between the average responses of the sample members about the challenges of the glass ceiling, which are attributed to the different variables: (leadership position, academic degree, number of years of work experience leadership). In addition, to identifying ways to overcome the challenges facing women academic leaders from their point of view. To achieve the goal of the study; a questionnaire consisting of (33) phrases was used, divided into two axes. They are: (Professional challenges dimension - Personal challenges dimension). It was distributed to a sample of (46) women academic leaders in the faculties of King Khalid University. The study reached a set of results. The most important of which are that the study sample’s members gave a degree of agreement (to a high extent) on the existence of professional challenges, a degree of agreement (to a low degree) on the presence of personal challenges, and agreed (to a high extent) on ways to overcome the challenges facing academic leaders . The study also proved that there were no statistically significant differences for all study variables. In light of the results, the study made several recommendations.
Keywords: القيادات النسائية -- المرأة السعودية -- التعليم الجامعي -- أدوار المرأة